MONITORING TRAFFIC DAN MANAJEMEN BANDWIDTH JARINGAN KOMPUTER PADA BADAN SAR NASIONAL MENGGUNAKAN APLIKASI PRTG - Astriana Mulyani; Afin Fiyantono (Jurnal Techno Nusa Mandiri, 2014)
Network problems are often experienced at the National Sar Agency is often Downtime (Slow Time Access) on a computer network, the National Sar Agency itself has not been any applications used to monitor traffic and bandwidth management of computer networks, therefore monitoring the computer network in the transfer Downtime Data on the Board of the National Sar is in need is by way of Monitoring Traffic and Bandwidth Management Agency Network on National Sar. To be able to Maximize performance Internet network at the National Sar Agency. Therefore the application PRTG is in need of the Agency for National Sar as a function of monitoring the host server or router, so that each host can be monitored at any time in order to facilitate the performance of administrators in monitoring every existing host central office and branch offices.